Recent Advances in Drug Addiction Research and Clinical Applications 2016
DOI: 10.5772/63389
|View full text |Cite
|
Sign up to set email alerts
|

Review of Current Neuroimaging Studies of the Effects of Prenatal Drug Exposure: Brain Structure and Function

Abstract: Neuroimaging tools have provided novel methods for understanding the impact of prenatal drug exposure on brain structure and function and its relation to development and behavior. Information gained from neuroimaging studies allows for the investigation of how prenatal drug exposure alters the typical developmental trajectory. The current prevalence and characteristics of prenatal drug exposure and its implications for vulnerable periods of brain development are reviewed. Structural and functional neuroimaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 137 publications
(178 reference statements)
0
1
0
Order By: Relevance
“…Screening for FASD should not stop among those individuals who present a clinical history of prenatal exposure to drugs. It is important for SVP evaluators in this situation to investigate further because prenatal exposure to drugs most often involves PAE and research has found that PAE results in more severe functional deficits than exposure to common drugs of abuse (Ross et al., 2015; Thompson et al., 2009; Willford et al., 2016).…”
Section: Implications For Forensic Practicementioning
confidence: 99%
“…Screening for FASD should not stop among those individuals who present a clinical history of prenatal exposure to drugs. It is important for SVP evaluators in this situation to investigate further because prenatal exposure to drugs most often involves PAE and research has found that PAE results in more severe functional deficits than exposure to common drugs of abuse (Ross et al., 2015; Thompson et al., 2009; Willford et al., 2016).…”
Section: Implications For Forensic Practicementioning
confidence: 99%